2016
DOI: 10.1021/jacs.6b05191
|View full text |Cite
|
Sign up to set email alerts
|

Connectosomes for Direct Molecular Delivery to the Cellular Cytoplasm

Abstract: Transport of biomolecules, drugs, and other reagents across the cell's plasma membrane barrier is an inefficient and poorly controlled process, despite its fundamental importance to biotechnology, cell biology, and pharmaceutics. In particular, insufficient membrane permeability frequently limits the accumulation of drugs and reagents in the cytoplasm, undermining their efficacy. While encapsulating drugs in particles increases uptake by cells, inefficient release of drugs from these particles into the cytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 60 publications
3
49
1
Order By: Relevance
“…In order to obtain E‐GPMVs with a modified membrane and inner cavity, we simultaneously equipped them with a small hydrophilic fluorophore (CellTracker Deep Red Dye, referred herein as CTDR) and Chol‐PEG5000‐FITC polymer. First, the fluorescence intensity associated with CTDR alone indicates its successful transfer to the inside of the E‐GPMVs in a concentration dependent manner, in the range 1 × 10 −6 to 10 × 10 −6 m (Figure S6, Supporting Information), and is in agreement with the previously reported transfer of low molecular weight compounds present in the cytoplasm of the donor cells . However, we observed that this process is not linear, but exponential, and thus by controlling the number of desired molecules in the donor cell cytosol, it is possible to control their final amount inside E‐GPMVs, which is a necessary step when reactions have to be implemented inside MFs.…”
Section: E‐gpmvs With Simultaneously Modified Membranes and Cavitiessupporting
confidence: 90%
See 4 more Smart Citations
“…In order to obtain E‐GPMVs with a modified membrane and inner cavity, we simultaneously equipped them with a small hydrophilic fluorophore (CellTracker Deep Red Dye, referred herein as CTDR) and Chol‐PEG5000‐FITC polymer. First, the fluorescence intensity associated with CTDR alone indicates its successful transfer to the inside of the E‐GPMVs in a concentration dependent manner, in the range 1 × 10 −6 to 10 × 10 −6 m (Figure S6, Supporting Information), and is in agreement with the previously reported transfer of low molecular weight compounds present in the cytoplasm of the donor cells . However, we observed that this process is not linear, but exponential, and thus by controlling the number of desired molecules in the donor cell cytosol, it is possible to control their final amount inside E‐GPMVs, which is a necessary step when reactions have to be implemented inside MFs.…”
Section: E‐gpmvs With Simultaneously Modified Membranes and Cavitiessupporting
confidence: 90%
“…In order to establish the size distribution of E‐GPMVs, we supplement them with a fluorescent model membrane protein LcK tyrosine kinase‐GFP (Lck‐GFP) by genetically engineering HepG2 cells to overexpress this protein using a baculovirus gene transfer (BacMam 2.0) . When Lck‐GFP is successfully inserted, it preserves its fluorescence property, and does not affect the integrity of the membrane compartment (Figure S1, Supporting Information), in agreement with previous reports about the insertion of gap junction proteins in the membrane of giant plasma membrane vesicles . E‐GPMVs are isolated with a size range of 2–20 µm, as demonstrated by confocal laser scanning microscopy (CLSM) and flow cytometry data ( Figure A–C).…”
Section: Strategy To Create Mfs With Architecture and Functionality Asupporting
confidence: 83%
See 3 more Smart Citations